Unfinished Spaces - Korózs, Dóra; Zombor, Gábor (International Journal of Engineering and Management Sciences, 2016)
My paper studies unfinished spaces . My research is mainly focused on defining the concept of space and the adaptive characteristics of it. It also tackles the issue of "being unfinshed" based on various aspects and perspectives.